2019
DOI: 10.1177/1362168819862132
|View full text |Cite|
|
Sign up to set email alerts
|

Finding success with pedagogical innovation: A case from CSL teachers’ experiences with TBLT

Abstract: This study uncovers the under-explored influences that encourage teachers to incorporate task-based language teaching (TBLT) for teaching Chinese as a second language, and the process of teachers’ pedagogical attempts at a Chinese university. Activity Theory (Engeström, 1987) was adopted as the conceptual framework. As a qualitative study, the analysis drew on data from interviews and classroom observations with eight teachers, and complemented by interviews with two directors and 17 students. The study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In summary, the findings show that the STs had variable levels of understanding of task features ranging from vague to more accurate accounts of task features. This study supports the findings reported by Peng and Pyper (2019)…”
Section: The Lesson Plans Designed By the Stssupporting
confidence: 94%
See 1 more Smart Citation
“…In summary, the findings show that the STs had variable levels of understanding of task features ranging from vague to more accurate accounts of task features. This study supports the findings reported by Peng and Pyper (2019)…”
Section: The Lesson Plans Designed By the Stssupporting
confidence: 94%
“…Moreover, the word outcome can be misinterpreted by the STs as any end-result of doing tasks or activities. Similarly, the often missing features of the gap and the outcome is also reported in Peng and Pyper's (2019) study. Many activities claimed as tasks by teachers in their study often failed to meet these criteria.…”
Section: The Lesson Plans Designed By the Stssupporting
confidence: 71%
“…They also found that the less experienced teacher was more likely to be open to the reform and innovation than the other two more experienced teachers. Some other studies found that teachers tried their best to make the curriculum reform successful, such as those in studies of Nguyen et al (2018) and Peng and Pyper (2019). Nguyen et al (2018) found that Vietnamese EFL teachers in a selective school made considerable efforts to adapt or replace textbook tasks to make them more authentic and practical to their learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The passages can be used as tasks which can be deploy in the class. Peng and Pyper (2019) showed that the possible effects leading Chinese teachers to embody TBLT in the classrooms proved to be a success. These all become attractions for the learners to find out more about these linguistically information-coated materials deployed by the instructors in the classes the prominent of which are literary ones as Azizur ( 2019) has asserted that English language teaching material can be developed using a literary text.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%